Entropy and modular Hamiltonian for a free chiral scalar in two intervals - Arias, Raúl Eduardo (2018)
We calculate the analytic form of the vacuum modular Hamiltonian for a two interval region and the algebra of a current j(x)=∂φ(x) corresponding to a chiral free scalar φ in d=2. We also compute explicitly the mutual information between the intervals. This model shows a failure of Haag duality for two intervals that translates into a loss of a symmetry property for the mutual information usually associated with modular invariance. Contrary to the case of a free massless fermion, the modular Hamiltonian turns out to be completely nonlocal. The calculation is done diagonalizing the density matrix by computing the eigensystem of a correlator kernel operator. These eigenvectors are obtained by a novel method that involves solving an equivalent problem for a holomorphic function in the complex plane where multiplicative boundary conditions are imposed on the intervals. Using the same technique we also rederive the free fermion modular Hamiltonian in a more transparent way.